Creation of Lantiang Tiger Works Based on the Tiger Ilau Ritual - Nurwani Nurwani; Martozet Martozet (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Performing Artworktiger terinthe inspiration of the culture of catching tigers in the Minangkabau community. For the Minangkabau community, tiger has a special meaning called inyiak or ampang limo as a title. The Minangkabau people believe in having a strong relationship with tigers, and can protect humans and pets. The myth of the proximity of the Minang people to the tiger for the Minangkabau community is considered a truth and is believed to be the incarnation of their ancestors. Besides being believed by humans to have a close relationship with tigers, tigers are still wild animals that can prey on humans and livestock at any time. Tigers that are considered detrimental to the community because they have preyed on livestock or humans, will be caught by performing the tiger ilau ritual. The ritual of catching tigers is carried out with songs and incantations performed by shamans and mothers, with sad rhythms tending to lament. Ilau tiger ritual is the longest ritual, which is carried out for an indefinite period of time. The length of time sometimes takes fifteen days, it can be six months, it can even take up to a year. The unique and interesting phenomenon of tiger light, which has the meaning of cooperation, toughness, patience, resentment, fighting power, and hope, became the inspiration in the creation of Lantiang Harimau's works. Phenomenonthe Ilau tiger ritual event becomes the concept of work, which is poured throughs motiontiger blade. The tiger silat movement has a sharp, hard and deadly motion using tiger styles and moves, such as jumping and kicking, bouncing and pounced on by the tiger. This workworked on in a new form that was touched by incorporating modern elements in a contemporary context (Art Contemporary), without losing traditional values.